2019
DOI: 10.1111/jace.16886
|View full text |Cite
|
Sign up to set email alerts
|

Size‐induced grain boundary energy increase may cause softening of nanocrystalline yttria‐stabilized zirconia

Abstract: An increase in hardness with reducing grain sizes is commonly observed in oxide ceramics in particular for grain sizes below 100 nm. The inverse behavior, meaning a decrease in hardness below a critically small grain size, may also exist consistently with observations in metal alloys, but the causing mechanisms in ceramics are still under debate. Here we report direct thermodynamic data on grain boundary energies as a function of grain size that suggest that the inverse relation is intimately related to a size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
1
17
2
Order By: Relevance
“…Figure 5 shows the aforementioned cross‐sections where all samples present a network of sub‐surface cracks which indicate load energy accommodation as in the quasi‐plasticity model 8,9 . The density of cracks apparently reduces as the grain sizes increase in both S‐ZAO and E‐ZAO, suggesting differences in the energy absorption mechanisms for large and small‐grained samples, which is consistent with previous reports 9,19,20,40 . Long lateral cracks are present at small grain sizes in S‐ZAO (S‐H12 and S‐H15).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Figure 5 shows the aforementioned cross‐sections where all samples present a network of sub‐surface cracks which indicate load energy accommodation as in the quasi‐plasticity model 8,9 . The density of cracks apparently reduces as the grain sizes increase in both S‐ZAO and E‐ZAO, suggesting differences in the energy absorption mechanisms for large and small‐grained samples, which is consistent with previous reports 9,19,20,40 . Long lateral cracks are present at small grain sizes in S‐ZAO (S‐H12 and S‐H15).…”
Section: Resultssupporting
confidence: 85%
“…The low activation energy for fracture manifests itself as a decrease in hardness following the inverse Hall‐Petch relation. This proposed relationship between grain boundary energy (or grain boundary strength) and Hall‐Petch behavior suggests that the inverse Hall‐Petch relation could be mitigated by avoiding an increase in grain boundary energy, suggesting ‘colossal’ hardening may be achieved in nanoceramics 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] This may be due to an increase in the proportion of triple junction, which is related to changes in energy dissipation and fracture behavior. Bokov et al 46 found that inverse Hall-Petch relationship is correlated with the increased triple joint population as grain size decreases, and the increased triple joint population affects the excess energy of grain boundary. In terms of thermodynamic, the excess energy of grain boundary correlates with boundary stability.…”
Section: Energy (E B ) On Mechanical Propertiesmentioning
confidence: 99%
“…The critical grain size d c for this transition can depend on the structure and energy of GBs and their chemical composition. Indeed, recent experiments on nanocrystalline YSZ ceramics [11] demonstrated a significant increase in the GB energy with a decrease in grain size below the critical grain size for the transition from the direct to the inverse Hall-Petch dependence for hardness. This situation is similar to that for nanocrystalline metallic alloys where high-energy (nonequilibrium) GBs decrease the yield strength and hardness by promoting GB sliding, while reducing GB energies via lowtemperature annealing increases the strength and hardness of such solids [29 -31].…”
mentioning
confidence: 99%